Promoting business incubation for improved competitiveness of small and medium industries in Korea. (7th July 2005) - Kim, Hong; Lee, Yun-Jae; Ames, Michael D.
The Korean Government decided to increase the number of new start-ups by providing financing, man-power, technology and marketing support to compensate for the weakness of small and medium companies. As a new engine of technological innovation and economic development, the high-tech ventures have been attracting greater attention from government, industry and universities in Korea. Now fostering entrepreneurship and promoting new venture creations have become priority policy actions. With the economic crisis under IMF bailout in Korea, business incubators (BI) in Korea are under more pressure to make significant contributions to the national economy. Now BI are sprouting up rapidly in Korea. During the last 7 years, the number of BI has grown very rapidly and almost 350 incubators are now in operation. Because the majority of BI in Korea are in the infant stage, there is room for improvement. Based on the identified problems faced by BI, policy directions are suggested.